Detection, Risk Assessment, and Survey of Four Polycyclic Aromatic Hydrocarbon Markers in Infant Formula Powder - Chenggang Cai; Pinggu Wu; Pingping Zhou; Dajin Yang; Zhengyan Hu (Journal of Food Quality)
A gas chromatography-mass spectroscopy (GC-MS) method was developed to assess the infant exposure assessment from four important polycyclic aromatic hydrocarbon (PAH) markers in infant formula powder: benzo[a]anthracene, chrysene, benzo[b]fluoranthene, and benzo[a]pyrene (collectively referred to as PAH4). The developed method required the addition of an isotopically labeled internal standard, sample extraction under alkali conditions, a saponification step, and a solid-phase extraction purification step. In a controlled spike test, the average recovery rates of PAH4 were 77.3% to 111.8% and the relative standard deviations were 4.8% to 14.2% (n = 6). The quantitative limit (LOQ) and detection limit (LOD) of the method were 0.5 and 0.1 μg·kg−1, respectively. The PAH4 content was analyzed in 30 commercially available infant formula powders. The PAH4 content was found to be in the range of 0.1 to 0.87 μg·kg−1. Combined with the daily intake of infant milk powder in China, the average and maximum daily exposure of BaP for stage-1 infants in China are 0.45 ng/kg.bw.d−1 and 1.9 ng/kg.bw.d−1 and the PAH4 values are 8.6 ng/kg.bw.d−1 and 18.6 ng/kg.bw.d−1, respectively. The PAH4 content in the tested infant formula powders sold in the China were sufficiently low, and all of the tested products were safe for consumption.